Forecasting Design and Principal Dimension Decision in Ship Design Using Parent Design Approach for Folding Boat - Adnyani, L.; Nurcholik, S.; Kurniawati, F.; Baital, M. (LPPM ITK, 2018)
In the Nawacita program of the Indonesia President, there is a spirit of accelerating the pace of economic growth in all areas, including tourism. In 2016, national income from the tourism sector rose to the fourth position under oil and gas, coal and palm oil. This program is followed up by areas that have great tourism potential, one of which is East Kalimantan. Most East Kalimantan area based on marine tourism, islands and rivers, it is necessary to create adequate facilities to attract more tourists as well as Bali such as in water sport facilities. One of the most famous water sport is kayaking in Sanur, Kuta, Benoa and others. Seeing the potential of marine tourism in East Kalimantan and the use of kayak already exist in Bali, it is necessary to design a kayak that can be utilized in tourist areas of East Kalimantan. The existing tourist areas in the East Kalimantan region have a long distance and isolated locations that require efficient luggage. Besides, the area has not supported tourism facilities and infrastructure needed by tourists. Therefore, the aim this research is to design a folding boar so that practical to be moved, light and easy for the owner to use it.